The effect of vortex generator insert and TiO2/Water nanofluid on thermal efficiency and heat transfer of flat plate solar collector. (October 2022) - Sarasar, Mohammad Bagher; Saedodin, Seyfolah; Rostamian, Seyed Hadi; Doostmohammadi, Mohammadreza; Khaledi, Omid
Abstract: In this study, the effect of water based nanofluid and Vortex Generator Insert (VGI) on the thermal efficiency of Flat Plate Solar Collector (FPSC) with the rectangular channel have been investigated experimentally. The experiment on a FPSC using TiO2 /Water nanofluid and VGI as well as its heat transfer characteristics analysis has been performed for the first time. The nanofluid has been used in concentration of 0.4 vol%. The thermal efficiency has been calculated based on the ASHRAE 2014 standard. The Performance Evaluation Criterion (PEC), Nusselt numbers, and pumping power have been assessed for different configurations and various volume flow rates. The results showed that the reduction of thermal dissipation was 28.26% when the nanofluid was utilized at volume flow rate of 3 lit/min. The optimal volume flow rate was obtained based on lowest thermal dissipation and highest optical efficiency by using nanofluid and VGI, simultaneously. At the optimal volume flow rate, the optical efficiency increased by 14.5%, and the thermal dissipation decreased by 42.46%. In addition, the maximum Nusselt number was obtained in this combination and the optimal volume flow rate. The maximum PEC was attained for TiO2 /water nanofluid at the volume flow rate of 3 Lit/min, which was 1.31.